Rumbos : herramienta para la planeación financiera de la vejez a partir de la metodología de pensamiento de diseño (2017)
Preparing financially for our old age is the mainly topic of this project. Initially, I wanted to explore what thoughts come across when we think about getting old. Among them were the increase in life expectancy, the emotionality associated with aging and the meaning of old age, the importance of financial planning, and the outlook of the retirement system in Colombia. Next, I revised literature on psychology, behavioral economics, and financial education, among others. This project turned out to be a designer's challenge to imagine and propose alternatives to help create new routes to design a life project. In order to limit this project, I selected a sample of persons that was determined mainly looking for people that belonged to the formal labor market and who had economic stability. I worked with an institution that is interested in providing their employees with aspects related to the financial performance in their savings for old age...